The Bare Minimum: The Reality of Global Anaesthesia and Patient Safety - Boyd, Nicholas; Hewitt Smith, Adam (World journal of surgery, 2016)
Current guidelines for the provision of safe anaesthesia from the World Health Organization and the World Federation of Societies of Anaesthesiologists (WFSA) are unachievable in a majority of low and middleincome countries (LMICs) worldwide. Methods Current guidelines for anaesthesia and patient safety provisions from the WHO and WFSA are compared with local ability to achieve these recommendations in LMICs. Conclusions Influential international organizations have historically published anaesthesia guidelines, but for the most part, without impacting substantial documentable changes or outcomes in low-income environments. This analysis, and subsequent recommendations, reviews the effectiveness of existing strategies for international guidelines, and proposes practical, step-wise implementation of patient safety approaches for LMICs.
Keywords: Bare Minimum; Global Anaesthesia; Patient Safety